Treatment Of Harvested Rainwater From Different Location Of Catchment Area By Using Zeolite, Limestone And Laterite Soil - Omar, Khairunnisa Fakhriah Mohd (2017)
Malaysia is blessed with huge amount of rainwater. However, the rainwater is not fully utilized and is abandoned as surface runoff. Generally, rainwater has low concentration of pollutants. A treatment is necessary prior to utilize the rainwater as a source of drinking water. This study was carried out to determine the performance of three natural mineral adsorbents, namely zeolite, limestone, and laterite soil to remove pollutants such as COD, turbidity, manganese, iron, lead, and E.coli. Preliminary batch studies were conducted to determine the optimum conditions for each parameter and adsorbents. Based on the results, zeolite was able to remove COD, manganese and lead at optimum condition with percentage removal of 74%, 80%, and 79%, respectively. In this study, the performance of limestone was undoubtedly shown good removal of heavy metals (namely manganese, iron, and lead). Besides, the limestone also has good removals on E.coli at optimum condition with 99% removal. However, limestone has poor removals for COD with only 48% of percentage removals. The performance of laterite soil was determined and the results demonstrated that it performs a good removal for all the parameters at optimum condition. The percentage removals of COD, turbidity, E.coli, manganese, iron, lead by laterite soil were 56%, 83%, 99.6%, 89%, 83%, and 76.8%, respectively. In this study, adsorption isotherm model and adsorption kinetic model were determined for the removals of each parameter by the adsorbents. Laterite soil was chosen as a filter media in column study to remove E.coli due to the good performance in batch study. The column study was conducted with 300mm bed depth and 20 mL/min of flow rate. The results demonstrated a good performance as the removal of E.coli was continuously occur with the percentage removal of 90 - 99% after 58 days of treatment, whereby the final concentration of E.coli almost complied with the allowable concentration as stated in "Malaysian Drinking Water Guidelines". Therefore, the study discovered that the rainwater has shown the potential as drinking water after being treated by laterite soil.